2019
DOI: 10.1002/fsn3.1280
|View full text |Cite
|
Sign up to set email alerts
|

Flours from Swedish pulses: Effects of treatment on functional properties and nutrient content

Abstract: Despite the high nutritional profile in pulses, pulse consumption in Sweden is still low. However, the recent increase in consumption of sustainable and locally produced food in Sweden is driving demand for a versatile, functional pulse‐based ingredient that can be incorporated into different food products. This study assessed different treatments (boiling, roasting, and germination) when preparing flour from domestically grown pulses (yellow pea, gray pea, faba bean, and white bean). Functional properties (wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Flour from raw pea : Whole dried yellow and gray peas were ground using a laboratory‐scale mill (Cyclotec 1093, Tecator, Sweden). Flour from boiled pea : Dried peas were soaked in tap water (1:3 w / v ) at room temperature for 14 h then boiled in water (1:5 w / v ) until they get soft (50 min for yellow pea and 35 min for gray pea; Ferawati et al, 2019). The boiled peas were dried in a convection oven at 50°C for 16 h. The dried boiled peas were ground (500 μm particle size) using the laboratory‐scale mill referred to above.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Flour from raw pea : Whole dried yellow and gray peas were ground using a laboratory‐scale mill (Cyclotec 1093, Tecator, Sweden). Flour from boiled pea : Dried peas were soaked in tap water (1:3 w / v ) at room temperature for 14 h then boiled in water (1:5 w / v ) until they get soft (50 min for yellow pea and 35 min for gray pea; Ferawati et al, 2019). The boiled peas were dried in a convection oven at 50°C for 16 h. The dried boiled peas were ground (500 μm particle size) using the laboratory‐scale mill referred to above.…”
Section: Methodsmentioning
confidence: 99%
“…arvense ) is an ancient and underutilized local pea variety in Sweden that is currently cultivated on a small scale (Hushållningssällskapet, 2013; Swedish Board of Agriculture, 2015). A previous study reported that flour from gray pea has similar functional properties as compared with flour from yellow pea (Ferawati et al, 2019). Additionally, gray pea had a higher amount of resistant starch and folate content (Ferawati et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations